2021
DOI: 10.31661/jbpe.v0i0.2104-1300
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Mortality of COVID-19 Patients based on Data Mining Techniques

Abstract: If Coronavirus (COVID-19) is not predicted, managed, and controlled timely, the health systems of any country and their people will face serious problems. Predictive models can be helpful in health resource management and prevent outbreak and death caused by COVID-19. The present study aimed at predicting mortality in patients with COVID-19 based on data mining techniques. To do this study, the mortality factors of COVID-19 patients were first identified based on different studies. These factors were confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Other study conducted [ 42 ] four ML techniques were trained based on 10,237 patients' data and, finally, SVM with the sensitivity of 90.7%, specificity of 91.4%, and ROC of 0.963% had the best performance. Moulaei et al [ 31 ] also predicted the mortality of Covid-19 patients based on data mining techniques and concluded that based on ROC (1.00), precision (99.74%), accuracy (99.23%), specificity (99.84%) and sensitivity (98.25%), RF was the best model in predicting mortality. After, the RF, KNN5, MLP, and J48 were the best models, respectively [ 31 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other study conducted [ 42 ] four ML techniques were trained based on 10,237 patients' data and, finally, SVM with the sensitivity of 90.7%, specificity of 91.4%, and ROC of 0.963% had the best performance. Moulaei et al [ 31 ] also predicted the mortality of Covid-19 patients based on data mining techniques and concluded that based on ROC (1.00), precision (99.74%), accuracy (99.23%), specificity (99.84%) and sensitivity (98.25%), RF was the best model in predicting mortality. After, the RF, KNN5, MLP, and J48 were the best models, respectively [ 31 ]…”
Section: Discussionmentioning
confidence: 99%
“…Moulaei et al [ 31 ] also predicted the mortality of Covid-19 patients based on data mining techniques and concluded that based on ROC (1.00), precision (99.74%), accuracy (99.23%), specificity (99.84%) and sensitivity (98.25%), RF was the best model in predicting mortality. After, the RF, KNN5, MLP, and J48 were the best models, respectively [ 31 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The LR algorithm is less efficient in their research (F - score = 82%) than in our findings (F - score = 87.5%).Other studies have been performed in Iran to diagnosis COVID-19 using ML algorithms that have used CT images dataset ( 39 ) or routine blood tests ( 40 ). Other studies based on ML algorithms in Iran in the field of predicting mortality ( 41 , 42 ) and intubation prediction ( 43 ) have been performed. The strength of our research compared to other research is the multi-center data set and the large volume of data set.…”
Section: Discussionmentioning
confidence: 99%